Kajian Upaya Mitigasi Struktural dan Nonstruktural Bencana Banjir di Kota Kendari - Wahid, Khalil Abdul (Journal of Geographical Sciences and Education, 2023)
The government and the community need to take various mitigation measures to reduce the impact and losses caused by flooding in Kendari City. This study aims to examine flood disaster mitigation efforts implemented in Kendari City. Qualitative descriptive research was applied and analyzed using the Miles and Hubermann analysis method. The structural mitigation efforts carried out between the Kendari City Government, stakeholders, and the community include the construction of river embankments, flood retention ponds, repair of the city's drainage system, installation of river water level monitoring devices, installation of flood-prone signs, and disaster evacuation routes, as well as the construction of embankments and modifications to the house building. Non-structural mitigation includes: making disaster regulations, conducting risk assessments, threats, and flood vulnerability, mapping disaster-prone areas and flood evacuation routes, assisting in research activities or research on flood disasters, forming Disaster Preparedness Groups, making appeals, cleaning rivers and drainage channels, conducting socialization activities and disaster training to the general public and school environment, as well as disaster insurance.